First principles study of the structural, elastic and electronic properties of Ti2InC and Ti2InN - Benayad, N.; Khenata, R.; Litimein, F.; Reshak, Ali Hussin; Rabah, M.; Baltache, H. (World Scientific Publishing Company, 2011)
Link to publisher's homepage at http://www.worldscinet.com/